2017
DOI: 10.1371/journal.pone.0184860
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting resting-state fMRI abnormalities from sickle and non-sickle anemia

Abstract: Sickle cell disease (SCD) is a chronic blood disorder that is often associated with acute and chronic cerebrovascular complications, including strokes and impaired cognition. Using functional resting state magnetic resonance images, we performed whole-brain analysis of the amplitude of low frequency fluctuations (ALFF), to detect areas of spontaneous blood oxygenation level dependent signal across brain regions. We compared the ALFF of 20 SCD patients to that observed in 19 healthy, age and ethnicity-matched, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“…Moreover, the dlPFC is a core region in the executive control network that is involved in working memory, cognitive flexibility, selective attention and response inhibition (Elliott, 2003). One might speculate that the observed alterations in dlPFC_LC functional connectivity might underlie executive function deficits and associated cortical changes reported in SCD (Chen et al, 2017; Coloigner et al, 2017; Downes et al, 2019, Downes et al, 2018; Schatz and Buzan, 2006; Scott Mackin et al, 2014; Swift et al, 1989; Vichinsky et al, 2010). High levels of noradrenaline via projections from the LC to the prefrontal cortex have been shown to impair prefrontal inhibitory functions critical for executive function (Xing et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the dlPFC is a core region in the executive control network that is involved in working memory, cognitive flexibility, selective attention and response inhibition (Elliott, 2003). One might speculate that the observed alterations in dlPFC_LC functional connectivity might underlie executive function deficits and associated cortical changes reported in SCD (Chen et al, 2017; Coloigner et al, 2017; Downes et al, 2019, Downes et al, 2018; Schatz and Buzan, 2006; Scott Mackin et al, 2014; Swift et al, 1989; Vichinsky et al, 2010). High levels of noradrenaline via projections from the LC to the prefrontal cortex have been shown to impair prefrontal inhibitory functions critical for executive function (Xing et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Brain imaging studies (Balci et al, 2012; Chen et al, 2017; Schatz and Buzan, 2006; Scott Mackin et al, 2014) have shown atrophy of the corpus collosum, frontal lobes, thalamus, and basal ganglia, in addition to increased resting-state functional connectivity (RS-FC) of the default-mode network (DMN) in children, that was associated with cognitive decline (Chen et al, 2017; Colombatti et al, 2016; Schatz and Buzan, 2006; Scott Mackin et al, 2014). Increased amplitude of low-frequency fluctuations (ALFF) in the orbitofrontal cortex, anterior cingulate cortex (ACC) and posterior cingulate (PCC) compared to anemic controls has also been observed (Coloigner et al, 2017). These cortical abnormalities may play key roles in rewiring central pain pathways and causing neuroplastic alterations, resulting in vulnerability for development of neuropathic pain (Brandow et al, 2013; Darbari et al, 2015; Dias Antunes et al, 2017; Gustin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although this investigation did not assess functional connectivity within large-scale networks, ALFF is a measure of the power or intensity of the BOLD signal, and can be another index of disease physiology ascertained through fcMRI. 54 In the largest cohort to date, to our knowledge, that is a purely pediatric population limited to HbSS and HbSβthal 0 genotypes without a history of overt stroke or vasculopathy, we expand upon these reports, identifying and characterizing differences in functional connectivity measures across 13 different functional networks using 3 different statistical approaches. Critically, we established an association between ongoing metabolic stress and functional connectivity, with a decrease in homotopy and functional connectivity within select networks as white matter OEF increased.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 More details of this preprocessing pipeline are described in previous publication. 27 Percentage change of the MR signal ΔBOLD is calculated as…”
Section: Image Pre-processingmentioning
confidence: 99%